Experimental Study of Subchronic Toxicity of Lanthanum Nitrate on Liver in Rats - Dong Chen; Ying Liu; Ai-Jun Chen; Yu-Xiu Nie (SAGE Publishing, 2003)
Wistar rats were divided into six groups, which were given La(NO 3 ) 3 at 20.0, 10.0, 2.0, 0.2, and 0.1 mg/kg, and the control group, which was given physiological saline, respectively, for six months. Pathological changes of liver were observed via light microscopy and transmission electron microscopy. Glutamic-oxalacetic transaminase, glutamic-pyruvic transitanase, gamma-glutamyl transferase, and alkline phosphatase activities in the serum were measured. Superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and malondialdehyde of liver were determined. The metabolic accumulation of lanthanum in rat liver was investigated via inductively coupled plasma mass spectrometry. Results showed no abnormal biochemical changes. In the group of 20.0 mg/kg La(NO 3 ) 3 , there were loss of weight, decrease of glycogen in the hepatocytes, denser matrix of the mitochondria, and deformation of the nuclei of some hepatocytes with different degrees and infiltration of inflammatory cells in the portal area. The higher was the dose, the higher was the number of bodies contain high electronic dense gravel-like granules, and secondary lysosomes with dense bodies were observed. In the group fed 0.1 mg/kg La(NO 3 ) 3 , intracellular glycogen showed an increasing tendency, particularly increased animal growth and increased activities of SOD and GSH-Px. The content of La in the liver increased regularly with increase in close and time of administration. The results further proved that low-dose La(NO 3 ) 3 produced some specific biologic effects. This study illustrated the influence of La(NO 3 ) 3 on rat liver at cellular and subcellular levels and it provides an experimental basis for the purpose of setting a reasonable standard for safely utilizing rare earth elements.